1982
DOI: 10.1093/clinchem/28.12.2423
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the o-phenylenediamine assay for horseradish peroxidase: effects of phosphate and pH, substrate and enzyme concentrations, and stopping reagents.

Abstract: Horseradish peroxidase, assayed with o-phenylenediamine, is irreversibly inactivated when incubated in phosphate buffer, 100 mmol/L, at pH 5. The inactivation depends on both duration and incubation and phosphate concentration. Phosphate was the most potent inactivator and citrate the least potent of a series of buffers tested. The inactivation is not attributable to ionic strength per se or to Na+ or K+. The observed inactivation did not occur at high concentrations (2500 nmol/L, 0.1 g/L) of enzyme; however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…According to the procedure, 0.05 mL samples was added and the HRP content in the samples was determined and the results are given in Table 4. Table 4 showed that the results of the catalytic RS assay were agreement with that of the spectrophotometry (11). HRP has been widely used in water treatment (30).…”
Section: Assay Of Samplessupporting
confidence: 68%
See 1 more Smart Citation
“…According to the procedure, 0.05 mL samples was added and the HRP content in the samples was determined and the results are given in Table 4. Table 4 showed that the results of the catalytic RS assay were agreement with that of the spectrophotometry (11). HRP has been widely used in water treatment (30).…”
Section: Assay Of Samplessupporting
confidence: 68%
“…Thus, it is important to develop a simple and sensitive method to detect its activity. Current methods for determination of HRP include voltammetry (1-3), chemiluminescence method (CL) (4)(5)(6)(7)(8), spectrophotometry (9)(10)(11)(12), fluorescence spectrometry (FS) (13,14) and flow injection analysis (FIA) (15,16). Using aniline as a substrate, the voltammetric method has high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Once shaken or vortexed, the samples were directly reconstituted with suitable buffer or lyophilized to remove the solvent from the system in the presence or absence of trehalose (0.012 mL of 23% trehalose in water) followed by reconstitution with buffer. Reconstituted proteins samples (protein–buffer and protein–SGnP samples with or without solvent treated) were used for their specific activity assay (see Supporting Information for details) 33, 34, 35. Catalytic activity was measured for reconstituted HRP/lipase samples.…”
Section: Methodsmentioning
confidence: 99%
“…Among the broad variety of organic and inorganic substrates of peroxidases, here four organic substrates were studied: the chromogenic substrates guaiacol (2-metoxiphenol) and ABTS, often used as reference substrates, and o-dianisidine and o-phenylendiamine, the latter three suitable for use in ELISA procedures that employ peroxidase conjugates [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%